2020
DOI: 10.3390/ijerph17082937
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Drama. Use of ICDAS II and Fluorescence-Based Intraoral Camera in Early Occlusal Caries Detection: A Clinical Study

Abstract: Background: Early diagnosis of occlusal caries is of paramount importance for a minimally invasive approach in dentistry. The aim of the present in vivo clinical prospective study was to compare the diagnostic outcomes of visual subjective evaluation between the International Caries Detection and Assessment System (ICDAS-II) and an intraoral fluorescence-based camera (VistaCam iX Proof, Dürr Dental, Bietigheim-Bissingen, Germany) for the detection of pits and fissures in early caries lesions of posterior teeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
11
0
4
Order By: Relevance
“…Em função de aumentar a base de conhecimento dos determinantes sociais, comportamentais e biológicos do ECC (Early Childhood Caries -ECC), os cientistas estão realizando o ZOE-G4S (Zero-Out Early Childhood Caries "Genes for Smiles"), que é um Research, Society andDevelopment, v. 9, n. 10, e36291110019, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.10019 estudo epidemiológico genético financiado pelo NIH (National Institutes of Health), desempenhado em uma grande amostra populacional de crianças em idade pré-escolar matriculadas nos centros Head Start na Carolina do Norte. A implementação desse protocolo clínico, ZOE 2.0, para a realização de uma pesquisa com crianças de 2 a 5 anos de idade, foi desenvolvido para coletar informações sobre a experiência de cárie dentária em nível superficial do dente e de defeitos no desenvolvimento do esmalte na dentição decídua.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Em função de aumentar a base de conhecimento dos determinantes sociais, comportamentais e biológicos do ECC (Early Childhood Caries -ECC), os cientistas estão realizando o ZOE-G4S (Zero-Out Early Childhood Caries "Genes for Smiles"), que é um Research, Society andDevelopment, v. 9, n. 10, e36291110019, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.10019 estudo epidemiológico genético financiado pelo NIH (National Institutes of Health), desempenhado em uma grande amostra populacional de crianças em idade pré-escolar matriculadas nos centros Head Start na Carolina do Norte. A implementação desse protocolo clínico, ZOE 2.0, para a realização de uma pesquisa com crianças de 2 a 5 anos de idade, foi desenvolvido para coletar informações sobre a experiência de cárie dentária em nível superficial do dente e de defeitos no desenvolvimento do esmalte na dentição decídua.…”
Section: Discussionunclassified
“…A eficácia do fluoreto de diamina de prata a 30% (Silver Diamine Fluoride -SDF) foi confrontada com o tratamento restaurador atraumático (Atraumatic Restorative Treatment -ART) no diagnóstico de cárie de dentina em molares decíduos (Vollú et al,2019). O tratamento ART foi desenvolvido em meados da década de 1980, o método possui três bases: educação para a saúde ; esforços para prevenção de doenças de cárie e gengivite; e técnica restauradora Research, Society andDevelopment, v. 9, n. 10, e36291110019, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.10019 atraumática, baseada nos princípios de intervenção mínima -MI ( Faustino-Silva, & Figueiredo, 2019). Crianças de 2 a 5 anos de idades, pré-escolares, com lesões ativas de cárie na superfície oclusal dos molares decíduos foram divididas aleatoriamente em dois grupos de testes: SDF e ART.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The International Caries Detection and Assessment System (ICDAS) was developed to standardize visual diagnosis and clinical management of carious lesions. It identifies caries lesions on the basis of their clinical visual appearance; the examination is aided by a ballended explorer and should be carried out on clean and dry teeth 3 . On the other hand, several modern devices are used to detect the presence of early dental caries lesion of which is DIAGNOCam which utilizes near-infrared light that can be used easily in all segments of dentition and was reported as an effective method for the diagnosis of occlusal caries without cavitation in permanent molar teeth 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of occlusal caries is of paramount importance for a minimally invasive approach in dentistry. The Special Issue showed that new technologies are fundamental in order to avoid underestimation [ 3 ]. New technologies for oral healthcare sustainability are clearly described by Palaia G [ 4 ] through use of the 445 nm diode laser, which proved to be a device that can be safely used for the biopsies of clinically unsuspicious lesions.…”
mentioning
confidence: 99%